Evaluación de la calidad microbiológica de extracto de Saccharum officinarum que se comercializa de forma ambulatoria en el distrito de Trujillo – La Libertad, Perú – 2018 - López Lara, Leonard (2018)
The microbiological quality of the extract of Saccharum officinarum, which is marketed on an outpatient basis in the district of Trujillo - La Libertad, Perú - 2018, was evaluated. Total Coliforms, Thermotolerants and E. coli were counted using the Number Plus method. Probable (NMP) using BRILA broth and triptoned broth for E. coli. The number of viable mesophilic aerobic bacteria was made by the plate count method in Plate Count Agar (PCA). The number of molds and yeasts in Oxytetracycline Glucose Agar (OGA). It was demonstrated that Total Coliforms (96%), Thermotolerant Coliforms (100%), E. coli (14%), aerobic mesophiles and the number of molds and yeasts exceed the permissible limits. The present work showed that the extract of Saccharum officinarum dispensed in the public road contains, in general, a microbial load that exceeds the permissible limits, making it from the microbiological point of view, not suitable for human consumption.